Proposition 187 and the Travel Ban: Addressing Economy, Security, and White Christian Nationalism in U.S. Christian Communities - Alexander, Laura E. (Religions, 2022)
The ideology of white Christian nationalism has become increasingly visible in the United States. This ideology intersects with public debate over immigration, posing a threat both to immigrants’ well-being and to American ideals of democracy. This essay considers how religious leaders in primarily white Christian communities addressed two historical moments related to immigration in the U.S.: Proposition 187 in California, and the "travel ban" instituted by the Trump administration in 2017. Christian leaders who supported Prop 187 and the ban, and those who opposed the two policies, tended to talk past each other when they discussed the issue of immigration and these specific policies. Pro-187 leaders used rhetoric of economic damage and pro-ban leaders used rhetoric of national security, whereas anti-187 and anti-ban leaders used rhetoric of hospitality and nondiscrimination. Christian leaders who opposed these policies attempted to apply the moral teachings of their religious tradition, but ethicists and religious leaders who wish to fully engage in conversation about immigration in the U.S. should incorporate discussion of economic and security concerns into their consideration of hospitality, in order both to address anxieties and to pull the veil back on racial and religious discrimination that hides behind these anxieties.